The mitotic regulator RCC2 promotes glucose metabolism through BACH1-dependent transcriptional upregulation of hexokinase II in glioma. (28th November 2022) - Liu, Tian; Wang, Yubing; Wang, Yiwei; Cheung, Stanley Kwok-Kuen; Or, Penelope Mei-Yu; Wong, Chi-Wai; Guan, Jingyu; Li, Zhining; Yang, Weiqin; Tu, Yalin; Wang, Jing; Ho, Wayne Lut-Heng; et al.
Abstract: Weighted gene co-expression network analysis (WGCNA) identified a cell-cycle module that is associated with poor prognosis and aggressiveness of glioma. One of the core members, Regulator of chromatin condensation 2 (RCC2) is a component of the chromosome passenger complex. Accumulating evidence suggests that RCC2 plays a vital role in the mitotic process and that abnormal RCC2 expression is involved in cancer development. Gene silencing experiments show that RCC2 is required for glioma cell proliferation and migration. RNA-Sequencing analysis reveals a dual role of RCC2 in both the cell cycle and metabolism. Specifically, RCC2 regulates G2/M progression via CDC2 phosphorylation at Tyrosine 15. Metabolomic analysis identifies a role for RCC2 in promoting the glycolysis and pentose phosphate pathway. RCC2 exerts effects on metabolism by stabilizing the transcription factor BACH1 at its C-terminus leading to the transcriptional upregulation of hexokinase 2 (HK2). These findings elucidate a novel PTEN/RCC2/BACH1/HK2 signaling axis that drives glioma progression through the dual regulation of mitotic cell cycle and glycolytic events. Highlights: PI3–K pathway transcriptionally upregulates the mitotic regulator RCC2 in human glioma. RCC2 enhances glucose metabolism and pentose phosphate pathway. RCC2 upregulates hexokinase 2 through stabilizing BACH1 transcription factor. RCC2 binds to the C-terminal domain of BACH1 and blocks its ubiquitination and degradation.